Competition and Complementarity of EU and FATF Beneficial Ownership Transparency Orders - Ates, Leyla; Knobel, Andres; Lorenzo, Florencia; Meinzer, Markus (Redefining Global Governance: A Tax, Trade and Investment Perspective in the EU and beyond, 2025)
The legal order of responses to the lack of beneficial ownership has gone beyond domestic to transnational norms. The Financial Action Task Force (FATF) and the EU are two prominent actors in this regard. Initially, the EU complemented the FATF only when it set its first international beneficial ownership standard in 2003. However, more recently, the EU has begun to differentiate its legal scope by taking measures ahead of the FATF’s standard in terms of the ambition to go beyond the status quo. Considering the overlap in geographic scope, such divergence means competition between the two transnational legal orders. This conclusion presents a challenge to the conventional view of the interdependent relationship between the anti-money laundering systems of two organizations. Such competition for transnational norm-making can spur the development of beneficial ownership transparency norms for the benefit of all nations. However, in 2022, the European Court of Justice resisted the EU’s standard-setter role in a preliminary ruling case brought by a national court. This shows that the EU must be aware of the recursive interaction between transnational and national judicial forums to develop a beneficial ownership transparency order that may interfere with the normative settlement. Otherwise, the EU falters its global standard-setter role.